The Effect of Giving Jagaq Porridge on Body Weight and Height of Stunted Toddlers Aged 12-24 Months in the Work Area of the Depar Health Center - Ririn Noviani Dewi; Umi Kalsum; Nursyahid Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of giving jagaq porridge on the body weight and height of stunted toddlers aged 12-24 months. This type of research is a quantitative research with a quasi-experimental research design with a one group pre-post test design. The population in this study were 11 stunted toddlers aged 12-24 months who were at the Dempar Health Center in 2022. The sampling technique used was total sampling. Data analysis technique using paired t-test. Based on the research results obtained, it can be concluded that there is an effect of giving jagaq porridge on body weight (p-value = 0.003) and height (p-value = 0.000) of stunted toddlers aged 12-24 months.